Christopher Columbus's Naming in the 'diarios' of the Four Voyages (1492-1504) : A Discourse of Negotiation - Gužauskytė, Evelina, 1975- (Book collections on Project MUSE., 2014)
In this fascinating book, Evelina Gužauskytė uses the names Columbus gave to places in the Caribbean Basin as a way to examine the complex encounter between Europeans and the native inhabitants.